Virtual Relationship in Moba-Based Game: Hyperreality of Intimacy Behind Anonymity in Mobile Legends Players - Wahdah Kamelia Salsabila (MOZAIK HUMANIORA, 2024)
The existence of games nowadays is not only for entertaining but also becomes virtual communication space. One of those games named Mobile Legends. This type of game is MOBA (Multiplayer Online Battle Arena) where communication among players determines victory. So that, its virtual communication can lead to a new cyberspace dynamic, namely virtual  relationships formed through MOBA-based games. It makes this game look-a-like a dating application. However, Mobile Legends player accounts are anonymous, making it not exactly the same as a dating application in terms of initiating relationships in cyberspace. Therefore, this study aims to find out what features lead to virtual dating in Mobile Legends. This research is an ethnographic research with Jean Baudrillard’s Hyperreality approach and some ideas about intimacy relations. Based on the research findings, there is a couple affinity feature characterized by a rose symbol on players who are paired in Mobile Legends. This affinity has the opportunity to encourage players to carry out dating activities in the game because this affinity level will go up based on the intensity they play together. In addition, it is likely that Mobile Legends players do not solely interpret account anonymity as arbitrary. Player’s self-image representation mediated through profile features and their gameplays constructed as identities that attracts emotional passion between players. These features and meanings then make Mobile Legends’ players who are in a relationship feel intimacy that exceeds real world’s intimacy.